Proposta de sinalização horizontal e vertical do município de José da Penha - RN - Paiva, Daniel Belarmino de (Universidade Federal Rural do Semi-Árido, 2018)
This work presents an analysis of the horizontal and vertical signaling of the municipality of José da Penha - RN. For this, a survey of data related to local traffic was made, thus seeking to highlight future problems that may occur due to increased traffic, untrained drivers, etc. And through photographic records to look for places that have signaling failures or the need to implement them based on the CONTRAN resolutions and manuals in this analysis. After the analysis with the help of the AutoCAD® 2015 student version, models will be made with the proposed signs for the critical points of the municipality: places that require more attention from the driver because they present difficulty in visualization or irregularities that make them dangerous to drivers. After all the analyzes and measures have been carried out, a signaling budget will be made, seeking a facilitation in the possible application of this work.
Monografia
Keywords: Motoristas; Trânsito; Análise; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA